Competitive Effects of Some Cations on Active Potassium Transport in the Human Red Blood Cell - Sachs, John R. (1967)
The effect of some cations on the active potassium transport system of the human red blood cell has been investigated. At low extracellular potassium concentrations, extracellular sodium competitively inhibits the active potassium influx at all sodium concentrations investigated, and tetraethylammonium behaves in a fashion similar to that of sodium. At low extracellular concentrations of potassium, ammonium at low concentrations at first stimulates the active potassium influx, but at higher concentrations inhibits it. Tetramethylammonium at most slightly stimulates the active potassium influx, and calcium is without effect. The behavior is consistent with a model in which potassium is required at more than one site before transport occurs, and the sites are indistinguishable as far as their behavior toward the ions investigated is concerned. The affinity of the alkali metal cations for the sites appears to be explicable in terms of their physical characteristics.